Trombositosis: Faktor Risiko Peningkatan Aterosklerosis pada Perokok Pasif di Kecamatan Pahandut Kota Palangka Raya - Rinny Ardina (Borneo Journal of Medical Laboratory Technology, 2018)
Passive smokers that exposure to cigarette smoke in their house has been reached 78,4%. Inhaled of cigarette smoke in the room was more dangerous than in an open place. Every puff of cigarette smoke from active smoker contains 1015 of free radicals which can cause oxidative stress. The presence of free radicals will trigger of activation of inflammatory genes, and then they can be activated of endothelial cells, dysfunction, and injury. Oxidative stress also stimulates large production of platelet (thrombogenesis) and followed by excessive formation of fibrin and thrombin. So that can cause thrombus in endothelial tissue, and it subsequently develops into atherosclerosis. This study aimed to describe thrombocytosis as a risk factor for increased of atherosclerosis in passive smokers in Kecamatan Pahandut, Kota Palangka Raya. This study used a descriptive observational method with a cross-sectional design. The sample obtained by 45 people with purposive sampling technique with criteria such as respondents were passive smokers, housewives, exposed to cigarette smoke more than five years, no history of the disease, and willing to become respondents. Examination of platelet counts was analyzed by an automatic method using Hematology Analyzer. The results showed that 6.7% of passive smokers had high platelet counts (thrombocytosis). High platelet counts in 6.7% of passive smokers caused by exposure of cigarette smoke from active smokers can endanger passive smoking, especially the risk of atherosclerosis. Therefore, a preventive and educative method for both passive and active smokers are needed to prevent the dangers of cigarette smoke to the risk of atherosclerosis